A new pedunculate barnacle (Cirripedia: Heteralepadidae) from the Mediterranean with notes on reproduction - Buhl-Mortensen, Lene; Mifsud, Constantine (Zootaxa, 2017)
Twenty-six specimens of Heteralepas were discovered attached to a derelict nylon mooring line recovered from 100–150 m depth off Malta in the Mediterranean Sea. These shell-less barnacles could be distinguished from the 28 previously described species of Heteralepas by the following combination of morphological characters: the relative lengths of the capitulum and peduncle; the presence of a clear demarcation between the capitulum and the peduncle; the capitulum ovoid and wrinkled but lacking tubercles and ridges; and the aperture large with crenulate or flaring lips. COI 18S, and 12S ribosomal RNA gene sequences from three specimens were compared with information for Heteralepas japonica (Aurivillius, 1892) available from GenBank, and the calculated p-distances were 15% and 8% respectively. On the basis of both morphological and molecular criteria, the proposal of a new species is justified, and herein we name and describe Heteralepas newmani, sp. nov., which is the only known member of the family Heteralepadidae from the Mediterranean Sea. Complemental males were attached to nine (35%) of the 26 hermaphrodite specimens, and data on their incidence (usually one but up to four when present) and positioning on the hermaphrodites are given. Two males of a parasitic isopod (Crinioniscidae) and six females of the same, probably undescribed, species and representing different states of maturity, were found within the mantle cavity of one hermaphrodite.